Penilaian Semula Nilai Koefisien Air Larian (C) Dalam Kaedah Rasional Menggunakan Alat Hujan Simulasi Di Permukaan Berbeza - @ Mohd Ghani, Mukhlisah Hanafi (2010)
The different values of peak discharge estimated in the Rational Method model is said to be caused by the various methods used in determining the runoff coefficient (C) parameter. The runoff coefficient value can be defined as the total amount of rainfall that is generated to become runoff. Various studies that have been conducted produced C values that differ from one to another. For example, the C values suggested by the Manual of Storm Water Management (MSMA) and the American Society of Civil Engineers (ASCE) were inconsistent or different, the landuse classification confusing, unorganized and not uniform, and also the application of suggested C value is still doubtful to be applied in Malaysia. Thus, this research focused on the estimation of C values based on the landuse classification for urban areas in Penang using a rainfall simulator. The runoff coefficient was generated from various surface types at a plot scale which represents the urban landuse. The results obtained show that the C value is 0.80-0.86 (asphalt), 0.84-0.91 (concrete), 0.77-0.90 (zinc), 0.72-0.84 (brick), 0.83-0.95 (asbestos), 0.79-0.90 (tiled roof), 0.21-0.39 (grass 2º - 7º) and 0.23-0.64 (bare soil 2º - 7º). The variation of C value was influenced by the total amount of rainfall, surface imperviousness, soil moisture, soil and surface characteristics, slope and vegetation cover. There are significant differences in the C value obtained in this study when compared to the C value of MSMA (asphalt, zinc, bricks, tiled roof, grass and exposed soil), and C value of ASCE (concrete and asbestos, grass and exposed soil). The four factors found to influence the differences of C values in this research are environment condition, scale, surface physical condition and soil antecedent moisture. Multiple Comparison test shows that there is a significant difference in the peak discharge estimated using Rational method compared to the gauged peak discharge. Nevertheless, peak discharge estimated from various C values in the Rational method does not show any statistical differences. As a conclusion, this study found that the rainfall simulator can be use as a suitable and efficient modus operandi in terms of cost and time for runoff studies.